Predictive value of early amplitude integrated electroencephalogram (aEEG) in sleep related problems in children with perinatal hypoxic-ischemia (HIE) - Qiuyan Tian; Yizhi Pan; Zheng Zhang; Mei Li; Li-xiao Xu; Min Gong; Po Miao; Xiaolu Jiang; Xiaofeng Yang; Chen-Xi Feng; Jian Pan; Yun Yu; et al. (BMC, 2021)
Abstract Background While great attention has been paid to motor and cognitive impairments in children with neonatal Hypoxic-Ischemic Encephalopathy (HIE), sleep related circadian rhythm problems, although commonly present, are often neglected. Subsequently, no early clinical indicators have been reported to correlate with sleep-related circadian dysfunction during development. Methods In this study, we first analyzed patterns of the amplitude integrated electroencephalogram (aEEG) in a cohort of newborns with various degrees of HIE. Next, during follow-ups, we collected information of sleep and circadian related problems in these patients and performed correlation analysis between aEEG parameters and different sleep/circadian disorders. Results A total of 101 neonates were included. Our results demonstrated that abnormal aEEG background pattern is significantly correlated with circadian rhythmic (r = 0.289, P = 0.01) and breathing issues during sleep (r = 0.237, P = 0.037). In contrast, the establishment of sleep-wake cycle (SWC) showed no correlation with sleep/circadian problems. Detailed analysis showed that summation of aEEG score, along with low base voltage (r = 0.272, P = 0.017 and r = -0.228, P = 0.048, respectively), correlates with sleep circadian problems. In contrast, background pattern (BP) score highly correlates with sleep breathing problem (r = 0.319, P = 0.004). Conclusion Abnormal neonatal aEEG pattern is correlated with circadian related sleep problems. Our study thus provides novel insights into predictive values of aEEG in sleep-related circadian problems in children with HIE.